GOOGLE MAPS: MAQASHID SYARIAH STUDY ON HOW TO DTERMINE THE DIRECTION OF COMTEMPORARY QIBLA - hendrifalak, hendrifalak; arifin, zainul; Ulin Nuha, Muhammad (ELFALAKY: Jurnal Ilmu Falak, 2023)
The advancement of this technology is the increasing number of alternative ways to determine the direction of the Qibla, one of which is by using an andoid cellphone in which there is a google maps application feature. but how to determine the direction of Qibla using google maps application is not many people know even though it can be said that almost all muslim communities have Android phones and have google maps applications. so in this article raised two formulations of the problem. First, how the analysis of Qibla direction determination using Google Maps application astronomical perspective. Second, how the analysis of Qibla direction determination using Google maps application Fiqh perspective. This research is of qualitative type with a focus on astronomy and fiqh studies. Primary Data is the result of observations and interviews related to determining the direction of Qibla using google maps application. with data analysis techniques used are descriptive-analytical. The study produced two findings. First, determining the direction of Qibla by using the google maps application is very easy with several stages, namely first looking for the Kaaba on the search menu and finding the location of our place where we are. for the determination of the direction of prayer with the Google maps application has weaknesses including the Qibla direction that can be determined with the google application can be used for buildings that are already standing. determining the direction of Qibla with Google Maps can only be applied to buildings, can not be applied to vacant land. Determination of the direction of Qibla with Google Maps on a large building that is clearly visible image, it will be easy to put the paper on the phone with the right, with reference to one / more sides of the building in the picture. Determining the direction of Qibla with Google Maps on a small building and the picture is not clear, it is difficult to put paper on the phone precisely, because it is not clear to see the reference to one/more sides of the building in the picture. Determining the Qibla direction with Google Maps on empty land cannot be applied. so that ijtihadong has been done using the google maps application, the intended direction of the results of this ijtihad makes a person more confident that he has been facing the Qibla. in fiqh dzan strong is something that can not be replaced by any doubt, in accordance with the rules اليقين َل يزال بالشك so long as a person has been convinced from the results of his Ijtihad that he is really facing the Qibla, then he has really been facing the Qibla and his prayer is valid.